(untitled) (Journal of Pharmaceutical Negative Results, 2016)
Introduction: The use of Asparagus adscendens (family:Liliaceae) root powder hasbeen reported traditionally for the treatment of epilepsy. But, it is yet to be validatedpharmacologically. Therefore, the present study was undertaken to explore theanticonvulsant effect of the roots in the experimental animal models of convulsions.Materials and Methods: The anticonvulsant effect of hydroethanolic root extract ofA. adscendens (AAE) was studied at 25, 50, and 100 mg/kg; intraperitoneally (i.p.)in maximal electroshock (MES), and at 25, 50, 100, and 200 mg/kg; i.p. doses inpentylenetetrazol (PTZ) test in mice. The duration of tonic hind limb extension (s) andlatency to tonic‑clonic convulsions (min) was noted in MES and PTZ tests, respectively.Phenytoin (25 mg/kg; i.p.) and diazepam (5 mg/kg; i.p.) served as reference standardsin MES and PTZ tests, respectively. Percentage mortality was also noted. Results: TheAAE treatment did not show any protective effect with regard to induction and durationof tonic hind limb extensor in MES test and latency to tonic‑clonic convulsions inPTZ test, as compared to their respective controls. Conclusions: The results obtainedfrom the experiments indicate that the AAE lacks anticonvulsant activity in MES‑ andPTZ‑induced convulsion tests